Phytochemical Profile, Antioxidant Potential, Antimicrobial Activity, and Cytotoxicity of Dry Extract from Rosa damascena Mill - Antoaneta Trendafilova; Plamena Staleva; Zhanina Petkova; Viktoria Ivanova; Yana Evstatieva; Dilyana Nikolova; Iliyana Rasheva; Nikola Atanasov; Tanya Topouzova-Hristova; Ralitsa Veleva; Veselina Moskova-Doumanova; Vladimir Dimitrov; et al. (Molecules, 2023)
Dry rose extract (DRE) obtained industrially by aqueous ethanol extraction from R. damascena flowers and its phenolic-enriched fraction, obtained by re-extraction with ethyl acetate (EAE) were the subject of this study. 1H NMR of DRE allowed the identification and quantitation of fructose and glucose, while the combined use of HPLC-DAD-ESIMS and HPLC-HRMS showed the presence of 14 kaempferol glycosides, 12 quercetin glycosides, 4 phenolic acids and their esters, 4 galloyl glycosides, 7 ellagitannins, and quinic acid. In addition, the structures of 13 of the flavonoid glycosides were further confirmed by NMR. EAE was found to be richer in TPC and TFC and showed better antioxidant activity (DPPH, ABTS, and FRAP) compared to DRE. Both extracts displayed significant activity against Propionibacterium acnes, Staphylococcus aureus, and S. epidermidis, but showed no activity against Candida albicans. Toxicity tests on normal human skin fibroblasts revealed low toxicity for both extracts with stronger effects observed at 24 hours of treatment that were compensated for over the following two days. Human hepatocarcinoma (HepG2) cells exhibited an opposite response after treatment with a concentration above 350 µg/mL for EAE and 500 µg/mL for DRE, showing increased toxicity after the third day of treatment. Lower concentrations were non-toxic and did not significantly affect the cell cycle parameters of either of the cell lines.